Controlling the HIV/AIDS epidemic: current status and global challenges - Demberg, Thorsten; Robert-Guroff, Marjorie (Frontiers in Immunology, 2012)
This review provides an overview of the current status of the global HIV pandemic and strategies to bring it under control. It updates numerous preventive approaches including behavioral interventions, male circumcision, pre- and post-exposure prophylaxis, vaccines, and microbicides. The manuscript summarizes current anti-retroviral treatment options, their impact in the western world, and difficulties faced by emerging and resource-limited nations in providing and maintaining appropriate treatment regimens. Current clinical and pre-clinical approaches towards a cure for HIV are described, including new drug compounds that target viral reservoirs and gene therapy approaches aimed at altering susceptibility to HIV infection. Recent progress in vaccine development is summarized, including novel approaches and new discoveries.